On Some Linguistic Peculiarities of Internet Slang - Madoyan, Narineh (Armenian Folia Anglistika, 2011)
The article examines the linguistic means of communication on the internet. While qualifying the linguistic expressions, the author of the article attaches importance to the analysis of the interrelation between language and slang. Based on the analysis of certain factual material it can be concluded that the language of the internet cannot be viewed as a type of a newly developing language. The article highlights the features typical of slang and generalizing these features, identifies the internet language as a type of slang.